2015
DOI: 10.3390/mi6111444
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Friction of Metals Using Laser-Induced Periodic Surface Nanostructures

Abstract: Abstract:We report on the effect of femtosecond-laser-induced periodic surface structures (LIPSS) on the tribological properties of stainless steel. Uniform periodic nanostructures were produced on AISI 304L (American Iron and Steel Institute steel grade) steel surfaces using an 800-nm femtosecond laser. The spatial periods of LIPSS measured by field emission scanning electron microscopy ranged from 530 to 570 nm. The tribological properties of smooth and textured surfaces with periodic nanostructures were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 45 publications
(60 reference statements)
1
28
0
Order By: Relevance
“…While the majority of scientific studies of LSFL on dielectric materials are based on punctual structures [12,15,27,28], i.e., LSFL are generated on a single spot only, for industrial applications, the generation of one-and two-dimensional LSFL is mandatory by scanning the laser. For metals [1][2][3][4]14,29,30] and semiconductors [5,[31][32][33], this has been shown in several publications because of the convenience in generating LSFL on these materials with free charged carriers ( < 0). For dielectric materials, e.g., fused silica, the authors recently have shown the transfer from punctual laser irradiation into the dynamic range, i.e., moving the laser spot over the sample [16].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…While the majority of scientific studies of LSFL on dielectric materials are based on punctual structures [12,15,27,28], i.e., LSFL are generated on a single spot only, for industrial applications, the generation of one-and two-dimensional LSFL is mandatory by scanning the laser. For metals [1][2][3][4]14,29,30] and semiconductors [5,[31][32][33], this has been shown in several publications because of the convenience in generating LSFL on these materials with free charged carriers ( < 0). For dielectric materials, e.g., fused silica, the authors recently have shown the transfer from punctual laser irradiation into the dynamic range, i.e., moving the laser spot over the sample [16].…”
Section: Introductionmentioning
confidence: 93%
“…Over the last few decades, Laser-Induced Periodic Surface Structures (LIPSS) have gained increasing attention due to the common availability of ultrashort pulsed laser sources. Additionally, intensified research has been raised by their widely diversified potential applications in wettability [1][2][3], tribology [4][5][6], cell cultivation [7][8][9] or anti-reflection coating [10]. These self-assembled structures were firstly reported by Birnbaum in 1965 after irradiation of a semiconductor with a polarized laser [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these tribological studies report on laser surface texturing for reducing internal torque in the lubricant friction regime and micro-dimpled laser textures were applied to function as micro-hydrodynamic bearings, micro reservoirs for lubricant retention or micro-traps for wear particles of sliding systems, for example, in seals, piston rings and thrust bearings [2][3][4][5][6][7][8]. Recent studies also report on the reduction of the coefficient of friction (COF) for ripples tested under lubrication friction conditions [9,10]. However, only little research has been spent so far on the increase of friction forces in dry friction contacts.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies also report on the reduction of the coefficient of friction (COF) for ripples tested under lubrication friction conditions [9,10]. However, only little research has been spent so far on the increase of friction forces in dry friction contacts.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the manifold potential applications of periodically structured surfaces, the aforementioned types of LIPSS have been intensively investigated on metals [7,8], semiconductors [3,4], and dielectrics [9][10][11]. Specifically, periodic surface structures can be used for controlling cell growth in biotechnology [12], friction and wear optimization [13], testing of mechanical properties [14], and influencing the emission properties of THz transmitters [15]. In particular, the influence of LSFL on the wetting properties of surfaces can be applied in microfluidics [16] and to self-cleaning components [17].…”
Section: Introductionmentioning
confidence: 99%